CASE REPORT: PENERAPAN SELF-MANAGEMENT KEPERAWATAN UNTUK MENCEGAH KEKAMBUHAN PADA PASIEN HIPERTENSI KRONIS - Prima Trisna Aji; Arief Sofyan Baidhowy; Zuniyati; Elinda Rizkasari (Institut Citra Internasional, 2025)
Background: Chronic hypertension is one of the most prevalent non-communicable diseases contributing significantly to global morbidity and mortality. Recurrent episodes frequently occur due to low patient adherence to self-management practices, resulting in poor blood pressure control. Objective: To report the implementation of a self-management-based nursing intervention aimed at preventing relapse among patients with chronic hypertension in a community setting. Method: This single-case report employed the nursing process approach encompassing assessment, diagnosis, planning, implementation, and evaluation. Medication adherence was measured using the Morisky Medication Adherence Scale (MMAS-8). The two-week intervention included education, training in self-monitoring of blood pressure, reinforcement of medication adherence, low-salt diet modification, light physical activity, and deep-breathing relaxation exercises. Results: The findings indicated a significant improvement in self-management ability, evidenced by a reduction in blood pressure from 160/100 mmHg to 130/80 mmHg and an increase in MMAS-8 score from 5 (low) to 8 (high). The patient also demonstrated full adherence to the therapeutic regimen, with the disappearance of dizziness complaints and improved sleep quality. Clinical implications: These results highlight the essential role of nurses in facilitating education-based and self-monitoring-centered self-management to prevent relapse in chronic hypertension. This approach can be integrated into community nursing practice programs as a sustainable strategy for chronic disease control.